Band edge smearing due to compositional disorder in multi‐component d ‐dimensional alloys. Issue 12 (21st October 2016) - Wiemer, M.; Jandieri, K.; Koch, M.; Gebhard, F.; Baranovskii, S. D.
Abstract : Modern optoelectronic devices are usually based on multi‐component alloys. Local statistical fluctuations in the concentrations of chemically different components cause energy fluctuations experienced by charge carriers. So far the theory for compositional disorder has been developed for compounds, in which atoms of only two chemically different types can occupy sites in a given sublattice. We extend the theoretical consideration for multi‐compound alloys containing more than two chemically different semiconductor species occupying sites in the same sublattice. Different spatial dimensionalities are considered. A comparison between theoretical predictions and experimental data can be used to reveal compositional dependencies of such material parameters as the effective mass. Abstract : Modern world cannot be imagined without optoelectronic devices, such as light emitting diodes or lasers based on semiconductor alloys. The larger is the number of alloy components, the easier is the adjustment of the structural and optical properties necessary for device applications. This flexibility, however, has its price – the compositional disorder. The paper shows how to estimate theoretically the energy scale of disorder in the multi‐component semiconductor alloys.